2023
DOI: 10.2217/cns-2023-0002
|View full text |Cite
|
Sign up to set email alerts
|

High-dose bevacizumab for radiation-induced brain necrosis: a case report

Abstract: Radiation-induced brain necrosis (RIBN) is a common adverse event from radiation therapy. We present a case of a 56-year-old man, diagnosed with non-small-cell lung cancer with brain metastases 2 years prior, for which he had received whole brain radiotherapy and brain stereotactic radiosurgery, who presented to the oncology unit with headache, dizziness and abnormal gait. MRI of the brain revealed radiological worsening of a cerebellar mass, including edema and mass effect. After a multidisciplinary tumor boa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In recent years, several studies have confirmed the efficacy of bevacizumab in the treatment of radiation‐induced brain necrosis. 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 A comprehensive meta‐analysis involving 12 studies showed that bevacizumab is effective in treating radiation‐induced brain edema, leading to improved clinical symptoms and superior outcomes in comparison to the corticosteroid treatment. 12 However, the majority of these studies were conducted with limited sample sizes, 13 , 14 , 15 leaving several questions unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have confirmed the efficacy of bevacizumab in the treatment of radiation‐induced brain necrosis. 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 A comprehensive meta‐analysis involving 12 studies showed that bevacizumab is effective in treating radiation‐induced brain edema, leading to improved clinical symptoms and superior outcomes in comparison to the corticosteroid treatment. 12 However, the majority of these studies were conducted with limited sample sizes, 13 , 14 , 15 leaving several questions unanswered.…”
Section: Introductionmentioning
confidence: 99%